Exploring leadership individual, organizational, and societal perspectives - Bolden, Richard (Oxford Oxford University Press, 2011)
Are leaders born or made? Does each society get the leaders it deserves? How--and why--is leadership "rhetoric" different from leadership in reality?
Includes bibliographical references and index.
Keywords: Leadership